Illusion of Control: Psychological Characteristics as Moderators in Financial Decision Making - Tobias Schütze; Ulrich Schmidt; Carsten Spitzer; Philipp C. Wichardt (Journal of Risk and Financial Management, 2024)
Financial decision making requires a sound handling of chance events. However, various studies have suggested that people are prone to illusion of control, i.e., the belief that prospects of a chancy event are better if they are involved in the randomisation process. This paper reports results from an experiment (N=420) suggesting that psychological characteristics moderate risk-taking behaviour under such circumstances. For example, we find that subjects high in sensation seeking buy more tickets of a risky lottery if they determine the winning numbers themselves and the random event lies in the future. The findings suggest that “illusion of control” effects are at least partly driven by underlying (idiosyncratic) emotions/preferences rather than an actual belief in control. Regarding applications, the results emphasise the importance of individual characteristics for the behaviour of decision makers in a financial context.
Keywords: 330; illusion of control; financial decision making; investment decisions; risk